American-Japanese relations in the twentieth century - صلاط أيمن (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
American-Japanese relations at the beginning of the twentieth century were characterized by friendly relations. During the Japanese-Russian war, the United States of America ended that war and concluded the Treaty of Portsmouth between the two parties. However, after a series of agreements between Japan and Russia later, Japan obtained privileges that conflicted with United States policy and provokedHer fears, and tension began between the two Countries.With the outbreak of World War I, the two countries were in the same camp during the war, and they worked to strengthen relations between them. In 1921, the United States of America called for the Washington Naval Disarmament Conference to be held for fear of war breaking out between them, but later Japan disavowed this Treaty and the Japanese-American confrontation becamepossible in Asia and relations between the two countries deteriorated. During World War II, the Japanese attacked the American port of Pearl Harbor and destroyed the American Pacific Fleet, but later the United States was able to direct several strikes against the Japanese and put an end to their progress. They demanded that the Japanese surrender without conditions, and after the Japanese ignored the warning, the United States dropped atomic bombs on the cities of Hiroshima.And Nagasaki, this incident marked the end of the war for Japan and the beginning of the American occupation. The American occupation of Japan ended after the San Francisco Conference, and with the help of the United States, Japan became a member of the General Trade and Customs Agreement and was accepted as a member of the United Nations.By the end of the twentieth century, American-Japanese economic relations were among the most important relations, and Japan seemed to be superior in this aspect, as it became the strongest economic Competitor to the United States of America.